Learning Model During Long Distance Learning - Sihaloho, Fahmi Ashari S. (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2021)
Online Distance Learning (ODL) is carried out because of the Covid-19 pandemic conditions which require people to carry out social distancing to reduce the risk of transmission. However, in the learning process, it still requires a learning model as a learning guide to achieve learning objectives so that students can achieve the desired competencies. In the 2013 curriculum, there are 3 learning models offered, namely Project Based Learning, Problem Based Learning and Discovery Learning. This research is a descriptive qualitative study that uses articles as data sources which are then compared as the author's ideas in terms of learning models in the ODL period. The results of this study indicate that the learning model offered in the 2013 Curriculum can still be used in online PJJ. However, it still has to be equipped with supporting tools and media so that the learning process can be carried out smoothly according to what has been planned